Frekuensi Minuman Tinggi Gula Dan Prestasi Akademik Anak SMP Di Kota Jayapura - Asriati, Asriati (Madu : Jurnal Kesehatan, 2025)
Excessive intake of high sugar in childhood and adolescence can increase the risk of cardiovascular disease and other chronic diseases. This study aims to determine the picture of the intake of high sugar drinks and the academic achievement of junior high school students. This type of research uses a cross-sectional survey conducted in April - August 2024. The data source in the study was primary data with 371 respondents of junior high school children aged 12-15 years in Jayapura City using the Multistage random sampling technique. Data analysis is using the chi-square test. The intake of high-sugar drinks in adolescents is mostly in the rare category (57.1%), and academic achievement is mostly in the moderate category (76.0%). There is a significant relationship between high sugar-drinks intake and academic achievement. The picture of high sugar drinks intake among junior high school children in Jayapura City is rare, however, with 43% of junior high school students often consuming high sugar drinks, it is hoped that schools will initiate activities that encourage teenagers to limit their high sugar drinks intake by providing healthy canteens at school, as well as encouraging parents of students to jointly restrict their consumption of high sugar drinks.